Falls and loneliness among Chinese older adults: evidence from a nationally representative longitudinal study - Zhiqiang Yu; Meng Jiang; Yueyun Zhang (Frontiers in Public Health)
BackgroundFalls and loneliness are both common during older adulthood and detrimental to older adults’ health. However, it remains unclear whether and how falls may be longitudinally related to loneliness among older adults, despite some cross-sectional evidence in both Western and Chinese contexts. This study aimed to examine the longitudinal association between falls and loneliness among Chinese older adults, its potential variation across age groups, and the role of social adaptation in mediating the association.MethodsData were from four waves of the China Longitudinal Aging Social Survey (CLASS, 2014–2020), and random-effects regression models were applied to a sample of 31,406 person-wave observations from 11,063 respondents. Both falls and loneliness were self-reported. Mediation analysis was conducted using the Baron and Kenny method and Bootstrapping procedures.ResultsFirst, falls were associated with higher levels of loneliness (p < 0.001). Second, the association differed by age group, with its magnitude being higher for the young-old (aged 60–69) (p < 0.05) and the oldest-old (aged 80 and over) (p < 0.01) than for the old-old (aged 70–79). Third, social adaptation played a mediating role (accounting for 10% of the total effect), that is, falls resulted in decreased social adaptation which further increased loneliness.ConclusionThese findings enrich our understanding of the pivotal role of falls in shaping the psychological well-being of older adults. In terms of policy relevance, falls prevention programs should be integrated into mental health initiatives for older adults, recognizing falls not merely as physical health events but as potential triggers for loneliness.